Guarding Against Fiscal Risks in Hong Kong SAR. (IMF Working Papers; Working Paper, 2007)
Hong Kong SAR's government faces the dual challenges of volatile revenue and medium term spending pressures arising from a rapidly aging population. Age-related spending pressures raise long-run sustainability concerns, while revenue volatility creates risks to service provision, possibly entailing sudden tax changes, or even requiring new borrowing. After describing the risks associated with aging, the paper uses value at risk techniques to measure the value of the unanticipated risks posed by volatile revenue. The paper also describes the self-insurance value of Hong Kong SAR's traditionally high fiscal savings (reserves), and the impact alternate policy choices could have on revenue volatility.